2020
DOI: 10.1101/2020.05.14.090738
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Endogenous formaldehyde scavenges cellular glutathione resulting in cytotoxic redox disruption

Abstract: 25Formaldehyde (FA) is a ubiquitous endogenous and environmental metabolite that is thought to exert 26 cytotoxicity through DNA and DNA-protein crosslinking. We show here that FA can cause cellular damage 27 beyond genotoxicity by triggering oxidative stress, which is prevented by the enzyme alcohol dehydrogenase 28 5 (ADH5/GSNOR). Mechanistically, we determine that endogenous FA reacts with the redox-active thiol group 29 of glutathione (GSH) forming S-hydroxymethyl-GSH, which is metabolized by ADH5 yielding… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 48 publications
1
3
0
Order By: Relevance
“…For example, in their paper, Zhu et al showed that FAsor lights up upon blocking GSH metabolism, indicating that GSH limits intracellular FA concentrations. This result supports recent findings showing that GSH synthesis prevents FA cytotoxicity 7 . Furthermore, FAsor could be applied to screen for drugs or compounds able to modulate the cellular levels of FA with therapeutic purpose.…”
Section: Fasor Comes To Shed Light Into Formaldehyde Biologysupporting
confidence: 93%
“…For example, in their paper, Zhu et al showed that FAsor lights up upon blocking GSH metabolism, indicating that GSH limits intracellular FA concentrations. This result supports recent findings showing that GSH synthesis prevents FA cytotoxicity 7 . Furthermore, FAsor could be applied to screen for drugs or compounds able to modulate the cellular levels of FA with therapeutic purpose.…”
Section: Fasor Comes To Shed Light Into Formaldehyde Biologysupporting
confidence: 93%
“…Combined treatment of L-BSO and N6022 resulted in little increase with no statistical difference ( Supplementary Fig. 6b, c), indicating that ADH5 and GSH synthesis might be epistatic for the control of intracellular FA 42 .…”
Section: Resultsmentioning
confidence: 96%
“…This result confirmed that the deficiency of FA metabolism in ALDH2/ADH5 inhibited cells disrupted FA homeostasis and caused cellular FA accumulation, which may lead to cell damaging effects in related diseases. In addition, a recent report showed that inhibition of GSH synthesis with L-BSO (L-Buthionine-Sulfoximine, an inhibitor of γ-glutamylcysteine synthetase) promoted the toxicity of FA to cells, especially in those with ADH5 knockout 42 . We thus treated HeLa cells with L-BSO and N6022 alone or together, and vehicle control, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…However, knowledge of the detailed mechanisms of cyanotoxins' impact, including disrupted metabolic pathways in the context of antioxidant systems, is still scarce. It was demonstrated that some other toxins such as arsenic species or formaldehyde might interfere with a crucial antioxidant system component, glutathione (GSH), in a potentially direct reaction, which can lead to harmful effects at the cellular level [25,26]. In our recent paper, we examined the influence of CYN or its decomposition products on GSH activity in a direct reaction.…”
Section: Introductionmentioning
confidence: 99%